The English edition of Hadrianus Junius’ Nomenclator (1585) - Stein, Gabriele (Lexicographica, 2006)
Der Artikel The English Edition of Hadrianus Junius’ Nomenclator (1585) wurde am 07.12.2006 in der Zeitschrift Lexicographica (Band 21, Heft 2006) veröffentlicht.
Gesehen am 14.01.2021